2018
DOI: 10.1016/j.jbankfin.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Control thyself: Self-control failure and household wealth

Abstract: In recent years, economic research has pointed out that self-control is a highly relevant concept for the study of household financial behavior. A number of studies find strong relationship between measures of self-control on the one hand and low saving rates or over-indebtedness of households on the other. These studies define self-control as the ability to resist temptation and provide theoretical justification and empirical evidence for its importance.In this paper we employ a more comprehensive definition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…It is clear that self-efficacy is critical to financial health, which is consistent with past mediation research. For instance, self-control and household wealth are positively correlated, and important factors in preventing self-control failure are planning, monitoring, and commitment to pre-set goals (Biljanovska and Palligkinis, 2018), which in turn are all facilitated by people’s confidence in their ability to enact action required to produce the desired outcome (Lown, 2011). Also, procrastination is related to conscientiousness, and a study found that self-efficacy mediated the effect of conscientiousness on subjective happiness (Strobel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that self-efficacy is critical to financial health, which is consistent with past mediation research. For instance, self-control and household wealth are positively correlated, and important factors in preventing self-control failure are planning, monitoring, and commitment to pre-set goals (Biljanovska and Palligkinis, 2018), which in turn are all facilitated by people’s confidence in their ability to enact action required to produce the desired outcome (Lown, 2011). Also, procrastination is related to conscientiousness, and a study found that self-efficacy mediated the effect of conscientiousness on subjective happiness (Strobel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…8 However, even in countries where, historically, contributing to funded pensions has been voluntary, automatic enrolment has started to gain ground, with the aim of offsetting the resistance of individuals with regard to retirement savings and of increasing savings rates. Biljanovska and Palligkinis (2017) strongly support the idea of automated transfers to saving accounts as a valuable tool for helping households commit to the plans they themselves have made. They also argue that providing households with adequate and comprehensible financial information is important for households' financial planning, as it supports their ability to plan, monitor and commit to pre-set goals.…”
Section: Myopia and Financial Literacymentioning
confidence: 63%
“…Moreover, they assert that it is important that individuals are taught how to plan, as the ability to plan is essential in setting goals and achieving them. Biljanovska and Palligkinis' (2017) research provides a valuable extension to the earlier research on how to motivate individuals to save for old age and how effective the chosen methods are. For instance, Madrian and Shea (2001) document that automatic enrolment significantly increased the rates of participation in 401(k) schemes.…”
Section: Myopia and Financial Literacymentioning
confidence: 99%
“…Self-control affects people's financial behavior and financial well-being. People with good self-control save more money for their future and have better chances of success in future (Biljanovska and Palligkinis, 2018;Ser-et al, 1973;Strömbäck et al, 2017). Initially our prime motive in this study was to find a link between self-control and financial well-being of Pakistani peoples, but the data showed that self-control has no direct impact on financial well-being.…”
Section: Discussionmentioning
confidence: 74%
“…People tend to get confused by conflicts between their actions and feelings, but inner strength develops self-control (Baumeister, 2002). Biljanovska and Palligkinis (2018), used three components of self-control; planning, monitoring and commitment and found that selfcontrol is strongly associated with household net wealth and financial distress. Self-control helps in decision making, strong will-power and success in future to be rich or influential.…”
Section: Self-control and Financial Behaviormentioning
confidence: 99%